Universitas Polemologi dan Perang Terakhir - T. Jacob, T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1984)
This article discusses the problem of war among men which at present in the form of nuclear warfare constitutes the greatest threat against humanity and the human ecosystem. In the present state of evolution of the arms race $25 000 per second is spent for manufacturing weapons and four tons of TNT per capita arc available in the world arsenal for everybody. The cost to kill a human being has been increasing steadily, and wars have been taking more and more victims, with larger proportions of civilians. Natural scientists and engineers are more involved in the research and development of weaponry, and consequently, less funds arid manpower are allocated in the social and welfare sectors.It seems strange that the awareness of nuclear threat, which is real and immediate, is very low in the Third World; however. the International Association of University Presidents had successfully adopted the proposal for the International Day of Peace in its Congress in Costa Rica, and the first President of Gadjah Mada University since the 1950s had called attention towards studies and social innovation for the purpose of world peace.The nuclear arms race, which is more likely to precipitate a nuclear war, and which has taken victims though it has not yet become a reality, in the form of less social expenditures, its psychological influence on the young generation living continuously under a nuclear threat, and itspotential danger against the global ecosystem and human existence, altogether pales the destruction of Hiroshima by Little Boy.More important is the impotence of medical measures in case of a nuclear war, so that the one and only step to be taken is prevention. In this connection we observed the growing world movements against nuclear war which include more non-political groups without ideological affiliation.Actions that could be taken by a university in the Third World is limhed to conducting studies on human aggression and conflict resolution, teaching the etiology of war and the preservation of peace. and scientific ethics both in the hard and the soft sciences, and creating public awareness that a nuclear war is far different than a conventional one, in scale as well as in impact. In addition, Key Words: peace studies Ã¢â¬â nuclear war -- scientific ethics Ã¢â¬â arms race Ã¢â¬â Hiroshimaefforts for the prevention of nuclear war in the developed countries should be sThis article discusses the problem of war among men which at present in the form of nuclear warfare constitutes the greatest threat against humanity and the human ecosystem. In the present state of evolution of the arms race $25 000 per second is spent for manufacturing weapons and four tons of TNT per capita arc available in the world arsenal for everybody. The cost to kill a human being has been increasing steadily, and wars have been taking more and more victims, with larger proportions of civilians. Natural scientists and engineers are more involved in the research and development of weaponry, and consequently, less funds arid manpower are allocated in the social and welfare sectors.It seems strange that the awareness of nuclear threat, which is real and immediate, is very low in the Third World; however. the International Association of University Presidents had successfully adopted the proposal for the International Day of Peace in its Congress in Costa Rica, and the first President of Gadjah Mada University since the 1950s had called attention towards studies and social innovation for the purpose of world peace.The nuclear arms race, which is more likely to precipitate a nuclear war, and which has taken victims though it has not yet become a reality, in the form of less social expenditures, its psychological influence on the young generation living continuously under a nuclear threat, and itspotential danger against the global ecosystem and human existence, altogether pales the destruction of Hiroshima by Little Boy.More important is the impotence of medical measures in case of a nuclear war, so that the one and only step to be taken is prevention. In this connection we observed the growing world movements against nuclear war which include more non-political groups without ideological affiliation.Actions that could be taken by a university in the Third World is limhed to conducting studies on human aggression and conflict resolution, teaching the etiology of war and the preservation of peace. and scientific ethics both in the hard and the soft sciences, and creating public awareness that a nuclear war is far different than a conventional one, in scale as well as in impact. In addition, Key Words: peace studies Ã¢â¬â nuclear war -- scientific ethics Ã¢â¬â arms race Ã¢â¬â Hiroshimaefforts for the prevention of nuclear war in the developed countries should be supported, and solidarity among men should be intensified for further cultural emancipation.upported, and solidarity among men should be intensified for further cultural emancipation.Key Words: peace studies - nuclear war - scintific ethics - arms race - hiroshima